EFFECT OF CHERRY LEAF (Muntinga calabora) BIOINSECTICIDES EXTRACT TOWARDS MORTALITY OF WORM SOIL (Agrotis ipsilon) AND ARMYWORM (Spodoptera exiqua) ON PLANT LEEK (Allium fistolum) - Binawati, Diah Karunia; Amilah, Susie (LPPM Universitas PGRI Adi Buana Surabaya, 2013)
Leek plant (Allium fistulosum) that grown at Village Treceh Sajen Mojokerto District Pacetoften suffer from some loss that caused by the attacks from pests such as worm soil (Agrotisipsilon) and armyworm (Spodoptera exiqua). The use of synthetic insecticides is very dangerous,because the residue will affect the health of consumers. Cherry plant (Muntinga calabura) containsactive substances such as tannins, saponins and flavonoids that can be used as bioinsecticides.This study aims to determine whether there is an effect of cherry leaf bioinsecticidesextract towards mortality of worm soil and armyworm in a in vitro manner, and to observe thegrowth of leek plant at harvest scallion age 2 months. The study design used is a CompleteRandomized Design, with 4 treatments using cherry leaf extract (0%, 2.5%, 5% and 7.5%), andgiven 6 replications. Samples of worm soil and armyworm caterpillars each are 120 which itsmortality will be observed for 24 hours. Leek plant sample are 60 plants. The results of dataanalysis showed a 24-hour LC50 value for worm soil is 4.240% and the 24-hour LC50 values forarmyworm is 3,434%. These results indicate that the cherry leaf extract is more effective toannihilate armyworm than it is to annihilate worm soil.To observe the effect of cherry leaf bioinsecticides treatment extract towards the growth ofleek plant leaves were harvested 2 months of age. Results of test F (0.024) indicates that there is asignificant effect of cherry leaf extract towards the growth of leek plants. The results of the LSDanalysis of these data showed that the P3 treatment with a concentration of 7.5% is the one thatproduces the best growth of the plant.